Perancangan Sistem Diagnosa Penyakit Ikan Hias Menggunakan Metode Forward Chaining - Wahyu Dharma Putra; Pahrizal Pahrizal; Khairullah Khairullah; Yulia Darnita (Jurnal Media Infotama, 2025)
The knowledge of farmers about the types of diseases that can attack Koi fish during cultivation is very small. Prediction of disease indications in Koi fish cultivation is an important thing for the success of cultivation. Disease prediction is obtained from facts in the cultivation process. Determining Koi fish disease can be an obstacle when the information known is not accurate. So an application is needed that has knowledge like an expert (specialist doctor). Forward Chaining is a mathematical theory for proof based on the function of belief and reasonable thinking, which is used to combine separate pieces of information (evidence) to calculate the probability of an event. The method used to obtain diagnostic results by sorting between general and specific symptoms. With this application, it is expected to be able to diagnose and provide treatment solutions like those done by experts